International diversification at home and abroad - Fang Cai; Francis E. Warnock (Deutsche Bundesbank, 2005)
We analyze foreigners' and domestic institutional investors' positions in U.S. equities. Controlling for many factors, we uncover a common preference for large firms and firms that are diversified internationally. The domestic preference for internationally diversified firms implies that investors might obtain substantial international diversification by investing at home. Using an international factor model, we show that exposure to foreign equity markets is indeed greater for domestic firms that are more diversified internationally, suggesting that at least some of the home-grown foreign exposure translates into international diversification benefits. After accounting for home-grown foreign exposure, the share of "foreign" equities in investors' portfolios nearly doubles, reducing (but not eliminating) the observed home bias.
Keywords: G3; G11; G15; 330; home bias; international portfolio allocation; foreign exposure; Portfolio-Management; Internationaler Finanzmarkt; Bias; Vereinigte Staaten; Welt